2011
DOI: 10.1158/1078-0432.ccr-10-2214
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect between Erlotinib and MEK Inhibitors in KRAS Wild-Type Human Pancreatic Cancer Cells

Abstract: Purpose The combination of gemcitabine plus erlotinib has shown a small but statistically significant survival advantage when compared to gemcitabine alone in patients with advanced pancreatic cancer. However, the overall survival rate with the erlotinib and gemcitabine combination is still low. In this study we sought to identify gene targets that, when inhibited, would enhance the activity of EGFR-targeted therapies in pancreatic cancer cells. Experimental Design A high-throughput RNAi screen was carried o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 57 publications
0
44
1
Order By: Relevance
“…Diep et al reported that combination treatments with erlotinib and MEK inhibitors RDEA119 or AZD6244 had significant synergistic effects only in pancreatic cancer cells with wild-type K-Ras but not in cells with mutant K-Ras [27] . Amiloride was found to potentiate the growth inhibition of erlotinib in all the selected pancreatic cancer cell lines independent of K-Ras gene status.…”
Section: Discussionmentioning
confidence: 99%
“…Diep et al reported that combination treatments with erlotinib and MEK inhibitors RDEA119 or AZD6244 had significant synergistic effects only in pancreatic cancer cells with wild-type K-Ras but not in cells with mutant K-Ras [27] . Amiloride was found to potentiate the growth inhibition of erlotinib in all the selected pancreatic cancer cell lines independent of K-Ras gene status.…”
Section: Discussionmentioning
confidence: 99%
“…MiaPaCa-2 cells were established from the tumor in pancreas of a Caucasian male and harbors the most commonly found KRAS G12D oncogenic mutations observed in PC patients. Phenotypically, these cells are large with abundant cytoplasm, display aneuploidy and possess a tendency to grow in multiple layers [55,56]. T3M4 cells were established from a primary exocrine pancreatic carcinoma of a Japanese male and were also found to harbor KRAS G61H oncogenic mutations.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of RAS leads to phosphorylation of RAF, which phosphorylates MEK, and then ERK. Diep et al 149 found a synergistic effect between erlotinib and 2 MEK inhibitors, compared to monotherapy, in pancreatic cell lines with wild-type KRAS. Others 150 found that MEK inhibition in pancreatic cancer leads to EGFR-mediated PI3K activation and sensitivity to combinations of MEK and EGFR inhibitors in pancreatic adenocarcinoma cell lines.…”
Section: Future Biomarkers In Pancreaticmentioning
confidence: 99%